Spatial assessment of economic housing units a study on the urban housing developments of General Santos City - Marcon, Priscilla Hannah A.
The aim of this study is to make flexible spaces available to growing families residing in low-cost housing units through an adaptive design, strategic fenestrations and planning of spaces. The rigid construction of the existing low-cost housing units is too expensive and unaffordable for the low-income families upon the extension and modification of spaces which costs funds these families could have spent for their daily expenses. This study was conducted in five (5) different economic housing subdivisions located in General Santos City with twenty (20) respondents from each with a total of one hundred (100) respondents. A key informant interview was conducted to measure the indoor spaces. The SQI calculator was used to assess the spaces within each unit. The data was then assessed using Pearson?s product-moment correlation to find significant relationships between the variables using SPSS. The study concluded that all of the subdivisions failed to provide the minimum standard of habitable spaces required for a 4-person house. Further studies should be conducted to better understand the impact of using adaptable designs in the long run.